2017
DOI: 10.1038/bmt.2017.229
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative conditioning regimens with combined of haploidentical and cord blood transplantation for myelodysplastic syndrome patients

Abstract: The purpose of this study was to evaluate the strategy of haploidentical (HID) stem cell combined with a small doses of umbilical cord blood (UCB) from a third-party donor transplantation (haplo-cord transplant) for treatment of myelodysplastic syndromes (MDS), by comparing with identical-sibling donor (ISD) transplantation. Eighty-five patients were included between January 2012 and December 2015, with a median 40 years old. Forty-eight patients received haplo-cord transplant and 37 patients received ISD tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 52 publications
2
20
4
Order By: Relevance
“…However, previous studies also have shown a significantly lower incidence of GVHD with dUCBT than with single UCBT [39], and also with haplo-cord HSCT than with haplo-HSCT and post-transplantation cyclophosphamide [16]. Moreover, another study using a similar protocol treating myelodysplasia syndrome found a lower incidence of GVHD than seen with HSCT from identical sibling donors (particularly the acute form) [40]. Similar to the foregoing conclusions, we believe that a disturbance in the balance between the protective role of regulatory T cells in UCB and the detrimental effect of the GVG response might be responsible for our observations.…”
Section: Discussionmentioning
confidence: 95%
“…However, previous studies also have shown a significantly lower incidence of GVHD with dUCBT than with single UCBT [39], and also with haplo-cord HSCT than with haplo-HSCT and post-transplantation cyclophosphamide [16]. Moreover, another study using a similar protocol treating myelodysplasia syndrome found a lower incidence of GVHD than seen with HSCT from identical sibling donors (particularly the acute form) [40]. Similar to the foregoing conclusions, we believe that a disturbance in the balance between the protective role of regulatory T cells in UCB and the detrimental effect of the GVG response might be responsible for our observations.…”
Section: Discussionmentioning
confidence: 95%
“…24 Recently, some studies show that HID transplantation combined with tp-UCB could result in rapid engraftment, low incidences of GVHD, and disease relapse of hematological malignancy. [14][15][16][17] Considering that UCB contains CD4 + CD25 + Tregs and mesenchymal stem cells etc. 25,26 These cells have an immune regulation mechanism that can regulates the hematopoietic microenvironment and therefore play an important role in the prevention of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 109 consecutive children with NMD underwent unmanipulated haploid HSCs combined with tp-UCB transplantation between January 2014 and December 2018. [14][15][16][17] The number of diseases were recorded, including BMFs (n = 62), PID (n = 33), IEM (n = 13), and malignant infantile osteopetrosis (n = 1). BMFs included SAA (n = 60), Diamond-Blackfan anemia (n = 1), and congenital dyserythropoietic anemia (n = 1).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tsai et al [31] reported that haplo/cord reduced-intensity transplantation followed by durable cord blood engraftment achieved similar outcomes compared with HLA-matched unrelated donor (MUD) in older AML and MDS patients. A group from China [32, 33] evaluated another combination strategy of un-manipulated haploidentical stem cells combined with a small dose of umbilical cord blood from a third-party donor (haplo-cord transplant) for hematological malignancies, which was followed by durable haploidentical stem cell engraftment. The results showed that haplo-cord transplant may potentially improve the outcome of HID- and UCB-HSCT alone.…”
Section: Discussionmentioning
confidence: 99%